Filosofi Barong Bulu Gagak Di Pura Dalem Kutuh, Desa Gulingan, Kecamatan Mengwi - I Putu Ariyasa Darmawan (Pramana: Jurnal Hasil Penelitian, 2021)
Bali has many Barong, one of which is Barong Ket. Dalem Kutuh Temple in Gulingan village has a Barong Ket who uses crow feathers. The six crow-feathered barongs in Bali are found at Dalem Kutuh Temple, Gulingan Traditional Village, Maspait Temple Banjar Singgi, Pakraman Intaran Village, Dalem Arum Temple, Banjar Nyelati, Kuwum Village, Mrajan Puri Tegal Tamu Batubulan, Pererepan Temple Banjar Bekul, Penatih Dangin Puri Village, and at Celangu Temple, Banjar Pekandelan, Bedulu Village, Gianyar. The function of the crow's feather barong at Dalem Kutuh Temple is to increase sradha and community service, protect. Barong and Rangda are implementations of the application of the concepts of totemism, animism, dynamism, pantheism, anthropomorphism, and monism, because all these concepts are a way for humans to understand the existence of God Almighty with very limited abilities, which are categorized as Saguna Brahman. The existence of the crow's feather barong at Dalem Kutuh Temple, Gulingan village, is able to bind norms and rules that reflect the value of good assumptions so that it functions as social control that is guided by community behavior. This control does not only apply to fellow believers, but also applies to managing community relations with God Almighty and with their environment.